(untitled) (Journal of the College of Basic Education, 2022)
A section of researchers saw that meaning has three levels, one of which is the literal meaning, or the linguistic meaning, which is the meaning taken from the meaning of words, pronouns and sentences, and the second is the meaning of speech, which is the contextual meaning, which corresponds to Arab linguists (the first meaning), and the third is the latent meaning Existing by force, which is the meaning of the speaker, and for Arab linguists it means (secondary meanings), and to clarify this, modern researchers gave the following example: If someone says to you: Is this your car? The context in which the question was mentioned indicates that the word (this) refers to a specific thing, which is the car, and the pronoun (k) refers to the addressee present, and although there is no problem in understanding the meaning of the syntax according to the first level, you may not have understood the meaning of the speaker.